EVALUATION OF ANTIOXIDANT CAPACITY AND TOTAL PHENOLIC CONTENT OF SELECTED MICROALGAE OF KUMAUN HIMALAYAN REGION - SHWETA NAILWAL; TAPAN KUMAR NAILWAL (International Journal of Pharma and Bio Sciences, 2013)
In order to identify new sources of safe and inexpensive antioxidants, the antioxidant capacity and total phenolic content of 5 microalgae isolated from fresh water lakes of Kumaun Himalayan Region were evaluated, using DPPH-Radical scavenging activity assay and the Folin-Ciocalteu method, respectively. The microalgae were extracted using methanol by a three step sequential extraction procedure. Most of these microalgae were evaluated for the first time for their antioxidant activities. It was found that microalgae Chlorella vulgaris and Mougetia parvula possessed the higher antioxidant activities and thus could be a potential rich source of natural antioxidants. In addition, the correlation coefficients between the antioxidant capacities and the phenolic content were very high (R2 = 0.9882). It is clear from the present investigation that phenolic compounds played key role in regulating antioxidant capacities of these microalgae.